Evidências de diálogos entre a educação do campo e educação ambiental em um curso de licenciatura - Borges, Patricia Spinassé (2022)
In Brazil, Public Policies on Environmental Education (EE) are planned for formal education covering basic and higher education. However, for the latter, they are still not adequately implemented. Thus, the research question is as follows: what is the evidence of the contributions of Environmental Education to the training of teachers of Natural Sciences at LEdoC UFG/Câmpus Goiás? The general objective of the thesis is to investigate the contributions of Environmental Education to the training of teachers of the degree course in Rural Education (LEdoC) - Natural Sciences, enabling a critical awareness of the socio-environmental problems present in the field. The specific objectives are: a) to identify the presence of Environmental Education and the relationship between the Environment and Sustainability in the Pedagogical Project of the Course (PPC); b) elaborate, develop, discuss and evaluate, in a participatory way, the proposal of an EE discipline for the LEdoC that considers the Alternation regime. For this, a qualitative approach research was carried out, in the participative research modality. The methodological procedures involved bibliographic surveys, document analyses, application of exploratory questionnaires and the elaboration, execution and participatory evaluation of the discipline “Environmental Education in Rural Education”. The data were submitted to content analysis, based on the markers: planning, historicity, environment, nature, sustainability, reflection, interdisciplinarity, dialogue, collectivity, culture, values, attitudes, participation, scientific knowledge, popular or traditional knowledge, educator environmental, constituting registration units generating the final categories: 1) Environmental Education and the training the Natural Sciences teacher in the field; 2) The importance of Alternation in teacher training in Natural Sciences. It was observed that the PPC provides for EE, in a transversal character, in the LEdoC curricular matrix, converging to the work of environmental issues associated with field phenomena; however this is partially effective in the proposal. It is noteworthy that the course “Environmental Education in Rural Education” confirmed the importance of EE in the training of Natural Science teachers through the identification and discussion of socio-environmental issues associated with field knowledge. Alternation, during Community Time, enables reflection, training and action in the development of EE activities and actions in rural schools and in the community, since the student will be able to experience the socio-environmental issues present in the field in locus. It is hoped that this thesis can contribute to the discussions and dialogue between EA and EC, aiming at training Natural Science teachers for schools and the rural community.